Assistance in Designing AI-Based Teaching Materials to Enhance Digital Literacy of Elementary School Teachers - Siti Fatimah, Asri; Marlina, Neni; Sulastri, Fera; Sri, Melisa; Ertinawati, Yuni (Civiliza Publishing, 2026)
This community service program is designed to enhance the digital literacy skills of teachers at SDN Mugarsari Tasikmalaya through the development of AI-based instructional material design. In today’s digital era, the integration of digital technologies in education has become essential. Technology has a significant impact on both teachers and students to improv the quality of learning fostering students’ skills and enhancing their learning motivation and self-confidence. However, it is found that many elementary school teachers still face challenges in using technology especially the use of artificial intelligence in developing learning materials. Therefore, continuous mentoring and intensive training are needed, particularly in the use of information technology as a tool for designing learning materials. There are various educational technologies that teachers can use in material design, such as videos, mobile devices, and AI-based applications. The use of artificial intelligence in education has recently become a widely discussed topic. AI-based technology offers great benefits and advantages due to its effectiveness, efficiency, and adaptability. The development of AI-based learning materials such as the use of ChatGPT, Magic School, Canva AI, and Quizizz AI can contribute on the development of learning quality to create more creative and relevant instructional content. This activity is expected to be beneficial to improve teachers’ readiness in facing the challenges of 21st-century learning in the future.